Drought tolerance of four vegetable crops during germination and initial seedling growth (Bioscience Journal, 2019)
Seeds of arugula (Eruca sativa Miller, cv. Cultivada), carrot (Daucus carota L., cv. Nantes), eggplant (Solanum melongena L., cv. Embú) and watermelon [Citrullus lanatus (Thunb.) Matsum. & Nakai cv. Crimson Sweet] were submitted to different osmotic potentials induced by polyethylene glycol (PEG) with the objective of evaluate the effects of drought stress on seed germination and initial seedling growth. Seeds were distributed in plastic boxes containing blotter paper, soaked with PEG solutions prepared with osmotic potentials 0.0 (control), -0.2, -0.4, and -0.8 MPa and kept into a seed germinator, at 25 °C for 14 days. A completely randomized design in a 4 Ã— 4 factorial scheme with four replicates of 50 seeds each was used. The results showed that by increasing of the osmotic potential level, germinated seeds number, germination rate index, root and shoot length, shoot and root dry matter, and seedling vigor indices decreased, while mean germination time and root: shoot ratio increased in all four vegetable crops. Additionally, the carrot and watermelon are more susceptible than arugula and eggplant to drought stress, with germination response declining more rapidly with the rise of osmotic potential level. Arugula and eggplant crops tolerate water stress of up to -0.2 MPa, without reducing germination of the seeds; however, the growth of shoots and roots are inhibited. The germination process of eggplant and watermelon seeds are completely inhibited at -0.8 MPa osmotic potential, whereas germination of carrot seeds is completely inhibited at -0.4 MPa osmotic potential. Severe drought stress limits the process of seed germination and initial seedling growth of vegetable crops.